2000
DOI: 10.1046/j.1524-475x.2000.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia‐reperfusion injury in chronic pressure ulcer formation: A skin model in the rat

Abstract: Most animal models of chronic pressure ulcers were designed to study only the role of ischemic injury in wound formation, often using single applications of constant pressure. The purpose of this study was to develop and characterize a reproducible model of cyclic ischemia-reperfusion injury in the skin of small un-anesthetized animals using clinically relevant pressures and durations. Ischemia-reperfusion injury was created in a 9 cm2 region of dorsal skin in male rats by periodically compressing skin under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(175 citation statements)
references
References 11 publications
3
166
1
5
Order By: Relevance
“…3), we observed that relieving the pressure initially resulted in increased perfusion (reactive hyperaemia) 4,29 as the blood returned to the affected tissue. When blood returns to the ischaemic tissue, it produces reactive oxygen species and free radicals that can accelerate cell death 30,31 . In our model, 1 h of pressure produced mild reversible tissue damage, and 3 h of pressure produced more severe irreversible damage.…”
Section: Resultsmentioning
confidence: 99%
“…3), we observed that relieving the pressure initially resulted in increased perfusion (reactive hyperaemia) 4,29 as the blood returned to the affected tissue. When blood returns to the ischaemic tissue, it produces reactive oxygen species and free radicals that can accelerate cell death 30,31 . In our model, 1 h of pressure produced mild reversible tissue damage, and 3 h of pressure produced more severe irreversible damage.…”
Section: Resultsmentioning
confidence: 99%
“…Other theories for the onset of tissue damage include collapse of capillaries and lymph nodes [29][30][31], reperfusion injury [32][33][34], and cell deformation under pressure [5,33,35]. The last has been studied using finite element (FE) models with a damage threshold law derived from previous experiments [4,36].…”
Section: Introductionmentioning
confidence: 99%
“…Reperfusion of blood to nutrientand oxygen-deprived tissue results in injury distinct from that caused by ischemic insult alone and has been implicated in distinct mechanisms of tissue injury that contribute to inflammation, vascular insufficiency, and ulcer formation [35]. Clinical evidence of reactive hyperemia in people with lower-limb amputation from prosthesis use dates back to 1962 [36].…”
Section: Discussionmentioning
confidence: 99%